Symptoms of Diabetes - Linda B. Bobroff (EDIS)
Type 2 diabetes is a growing health concern for children and adults in the United States. Diabetes that is uncontrolled can lead to blindness, kidney disease, heart disease, and amputations. Early diagnosis is critical! If you have any of the symptoms described in this fact sheet, see your health care provider right away! This 1-page fact sheet was written by Linda B. Bobroff and published by the UF Department of Family Youth and Community Sciences, July 2013.